Beginning iPhone 4 Development Exploring the iOS SDK - Mark, David; LaMarche, Jeff; Nutting, Jack (Apress : Imprint: Apress, 2011)
Beginning iPhone 4 Development is here! The authors of the bestselling Beginning iPhone 3 Development are back, with the same excellent material completely updated for iOS 4 and written from the ground up using the latest version of Apple's Xcode 3. All source code has been updated to use the latest Xcode templates and current APIs, and all-new screenshots show Xcode 3 in action. Beginning iPhone 4 Development is a complete course in iOS 4 apps development. You'll master techniques that work on iPhone, iPad, and iPod touch. We start with the basics, showing you how to download and install the tools you'll need, and how to create your first simple application. Next you'll learn to integrate all the interface elements iOS users have come to know and love, such as buttons, switches, pickers, toolbars, and sliders. You'll master a variety of design patterns, from the simplest single view to complex hierarchical drill-downs. The confusing art of table building will be demystified, and you'll learn techniques to save and retrieve your data using SQLite, iPhone's built-in database management system and Core Data, the standard for persistence that Apple brought to iOS with the release of SDK 3.   And there's much more! You'll learn to draw using Quartz 2D and OpenGL ES, add multitouch gestural support (pinches and swipes) to your applications, and work with the camera, photo library, accelerometer, and built-in GPS. You'll discover the fine points of application preferences and learn how to localize your apps for multiple languages. You'll also learn how to use the new concurrency APIs included in iOS 4, and make robust multithreaded applications using Grand Central Dispatch.   The iPhone 4 update to the best-selling and most recommended book for Cocoa touch developers   Written in an accessible, easy-to-follow style   Full of useful tips and techniques to help you become an iOS pro NOTE: For iPhone 4S or iOS 5 apps development, please instead check out the next edition of this book, Beginning iOS 5 Development - now available.